The Rise of Green Taxation: Global Intellectual Patterns and Emerging Research Agendas - Muhamad Luthfi Mubarok (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
Purpose: environmental taxation; green taxes; carbon pricing; sustainable development; bibliometric analysis. Research Design and Methodology: A comprehensive bibliometric analysis was performed on 398 Scopus-indexed publications (1990–2025) using RStudio and the bibliometrix package, incorporating performance metrics, thematic evolution, co-word networks, and conceptual structure mapping. Findings and Discussion: The results indicate a pronounced surge in scholarly output after 2015, coinciding with intensified climate policy commitments. Environmental taxation, carbon emissions, sustainable development, and environmental technology emerge as foundational themes, while motor themes illustrate an increasing convergence among fiscal instruments, innovation systems, and emissions mitigation strategies. Collaboration networks position China, the United States, and Europe as central nodes in global knowledge production. Implications: The evidence underscores the need to design environmental tax policies that integrate fairness, transparency, and technological capability to enhance societal acceptance and policy effectiveness. Future research should broaden linguistic and geographic coverage and employ mixed-methods designs to more fully capture the institutional and behavioral dynamics that influence tax implementation.